HUBUNGAN KOPING KELUARGA DENGAN TINGKAT KETAATAN DIET PASIEN DIABETES MELITUS DI PUSKESMAS - Made Desy Pratiwi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Dietary adherence is behavior of patients that directed to the instructions or the instructions given in the any prescribed therapy form. For patients with diabetes mellitus, adherence was defined as the activity, volunteerism, and involvement of patients in disease management with special care that agreed especially in diet adherence. This research is including to the quantitative research model, observational analytic study (non-experimental) type. This research was conducted on July 14 through July 19, 2014 towards diabetes mellitus patients in health centers I West Denpasar. The total sample utilized 58 people with the purposive sampling technique. The test is used to determine the relationship of independent variables and the dependent variable in this study is the Spearman rank correlation test (p value <?, ? = 0.05). The results of this study indicate that there is a relationship between family coping with the level of diet adherence of patients with diabetes mellitus (p value = 0.000) Based on the results of this research community nursing is expected to develop and apply a positive family coping in patients with diabetes mellitus especially in the dietary management level in order to adjust and improve the diet so that this research can be useful as a preventive action to prevent the complications of diabetes mellitus